Application Development for Cooperative Platform in Indonesia - Darmayadi, Andrias; Putri, Winda Ariska; Gani, Aliyyu; Nurapriliani, Anisa (Journal of Information System, Applied, Management, Accounting and Research; Vol 6 No 3 (2022): JISAMAR: August 2022, 2022)
The purpose of this research is to facilitate managers or cooperative members in managing cooperatives and facilitate the community to find various types of cooperatives in Indonesia to suit their needs through an application called M-Cooperative. To support this research, we use literature study methods or library studies conducted by collecting data from multiple sources such as from articles, journals, books, and other sources. The results showed that the Government was less concerned about cooperative development. But as we know, this cooperative is needed by the community. From the results, we try to give ideas related to the development of cooperatives in Indonesia based on digital applications. This is because the cooperative is open and close to the community. Of course, with this M-Cooperative can help all people. In addition, it can facilitate the community in the transaction indirectly so that the time and costs incurred can be more effective and efficient.